ANALISIS ALIH KODE DAN CAMPUR KODE PADA NOVEL MARIPOSA KARYA LULUK HF - RAHMAT KARTOLO SILITONGA (JURNAL ILMIAH SIMANTEK, 2021)
This study is a qualitative descriptive study with a sample of conversations in luluk HF's novel Mariposa. The data source inthis study is luluk HF's novel Mariposa. This research data is in the form of quotes of speech figures in the novel MariposaBy Luluk HF. The data collection technique in this study is to use library techniques, reading techniques and recordingtechniques. The instrument used is the author himself assisted by using data registrar cards, stationery, books and othermedia that support as a reference. Data validity techniques are source trianggulation and data trianggulation. The results ofthis study analysis showed that in luluk HF's novel Mariposa found pragmatic forms that are as follows the symptoms of codemix occurs in 2 directions, while code transfer symptoms occur in 1 one direction. The most dominant form of code mix is theinternal code mix form and the most dominant code transfer is the in-inside mixing of code. Factors causing code mixesinclude limitations on the use of code, the use of more popular terms, the place of residence and time of conversation andthe factors that cause the occurrence of code transfer include speakers or speakers, speech opponents, changes in thesituation.